Geochemical and Isotopic Characterisation of Actual Lacustrine Sediments from the Hydrothermal Lake Specchio di Venere, Pantelleria Island (Italy) - Marianna Cangemi; Paolo Madonia; Sergio Bellomo; Ygor Oliveri (Journal of Chemistry)
Hydrothermal lakes are a very common feature in volcanic environments, and among these lake Specchio di Venere (Pantelleria island, Italy) has attracted the interest of several researchers due to its peculiar characteristics. With the aim of improving the knowledge of its mineralogy, our work pointed out the characterisation of the bottom lake sediments. We collected and analysed 5 sediments cores around the shoreline, determining the mineralogical phases, concentration of major, minor, and trace elements, and the isotopic composition of carbon and oxygen in the carbonate phases. Our findings remarked a general compositional homogeneity in both the vertical and horizontal distribution of mineral phases, with the exception of peculiar geological niches connoted by biological and hydrothermal activities.